2012
DOI: 10.3844/ajessp.2012.403.411
|View full text |Cite
|
Sign up to set email alerts
|

The Correlations Between Mercury Speciation and Dissolved Organic Matter in the Sediment of the Red Sea

Abstract: This study addresses the correlations between Hg and organic matter in recent sediment; samples were collected from the Gulf of Aqaba, Red Sea coasts (oligotrophic regions) during 2010. In the present study TOC analyzer was used to determine Total Organic Carbon (TOC) and Total Nitrogen (TN) concentrations and the total amount of mercury (Hg T ) in sediment samples were analyzed by Hydra-C mercury analyzer. The obtained results indicated that, mercury, TOC and TN average concentrations in the Red Sea were 85.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Although some research has suggested that the structure of DOM may have an indirect impact on the rate of Hg photoreactions; however the exact mechanism of DOM is unknown that facilitates mercury reduction (O'Driscoll et al, 2006). A study conducted by Wedyan, Ababneh, and Al-Rousan (2012) established the fact that there is strong affinity between organic matter and mercury which is primarily related to the physical characteristic of these compounds and not to their chemical reactivity, these physical characteristics play the most significant role in the Hg distribution in the sediments. DOM facilitates the mobility of Hg across the column of water and sediment and also results in enhanced sequestration and concentrations of mercury in sediments (Wallschlager et al, 1996;Cossa & Gobeil, 2000).…”
Section: Dissolved Organic Mattermentioning
confidence: 99%
See 1 more Smart Citation
“…Although some research has suggested that the structure of DOM may have an indirect impact on the rate of Hg photoreactions; however the exact mechanism of DOM is unknown that facilitates mercury reduction (O'Driscoll et al, 2006). A study conducted by Wedyan, Ababneh, and Al-Rousan (2012) established the fact that there is strong affinity between organic matter and mercury which is primarily related to the physical characteristic of these compounds and not to their chemical reactivity, these physical characteristics play the most significant role in the Hg distribution in the sediments. DOM facilitates the mobility of Hg across the column of water and sediment and also results in enhanced sequestration and concentrations of mercury in sediments (Wallschlager et al, 1996;Cossa & Gobeil, 2000).…”
Section: Dissolved Organic Mattermentioning
confidence: 99%
“…The DOM in these sediments are consumed by different types of bacteria, as the mercury deposited under new layers of sediments and these bacteria live few millimeters under the water interface, a level where oxygen cannot reach. Chemical reactions that involve iron and sulfur are the source of energy for bacteria and these reactions also generate toxic byproduct which is methylmercury (Wedyan, Ababneh, & Al-Rousan, 2012). Accumulation of mercury in fish is a public health concern globally, reason being fishes are the primary source of toxic MeHg to humans.…”
Section: Dissolved Organic Mattermentioning
confidence: 99%